Evolution of environmental concerns in adjustment lending : a review - Warford, Jeremy...[et al] (World Bank WashingtonUS, 1994)
Reviews World Bank adjustment lending operations over the period FY88-FY92. Shows that environmental issues have become an important aspect in adjustment lending by the Bank.